Minority stress in people who identify as transgender: testing the minority stress model - Stennett, Sabrina (2016)
Objectives: People who identify as transgender are reported to experience high levels of mental health problems in comparison to people who do not identify as transgender. The minority stress model has been used to explain these high prevalence rates. But this model was designed to be used in lesbian, gay and bisexual (LGB) populations (Meyer, 1995, 2003). Researchers have applied some of the hypothesised processes of the model to people who identify as transgender. However, evidence testing the minority stress model in this population is limited. The model postulates that minority stress processes (namely, distal stress, internalised stigma, vigilance and concealment) lead to adverse mental health outcomes. It also states that coping and social support moderate and ameliorate the stress processes. However research on this aspect is inconclusive, with other researchers stating that coping and social support meditate the relationship between internalised stigma and psychological distress. In light of the current literature, this research aimed to test the application of the minority stress model in a sample of people who identified as transgender. It also aimed to test the moderating and mediating roles of coping and social support. Furthermore, this research endeavoured to develop an alternative model (i.e. based on the findings and the literature).